Ireland’s National Wage Agreements and Macroeconomic Performance: 1988–2008 - Leddin, Anthony J.; Egan, Paul G. (Statistical and Social Inquiry Society of Ireland, 2019)
This paper is a historical analysis of the role played by the seven National Wage Agreement’s (NWAs) in Ireland’s economic performance from their inception in 1988 to the Great Recession in 2008. The severity of the recession brought the partnership process, in this first phase, to an end. The pay awards were used to construct new, monthly nominal and real wage indexes for both the public and private sectors. The nominal indexes turn out to be significantly below the earnings data published by the CSO. The CSO earnings data contains “signal” plus “noise”. The “noise” element should be low but this is not the case. The assertion is that the derived pay award indexes give a more accurate measure of wage developments as the “noise” element is eliminated. A major difficulty with the NWA’s is that the partners are negotiating for nominal and not real (inflation adjusted wages), for a period of approximately three years into the future and cannot be revisited or be revised. The paper illustrates what unanticipated inflation did to the nominal wage awards. Between 1988 and the end of the Celtic Tiger period in mid-2000, the nominal wage awards increased by 50% but only by 5% after adjusting for inflation. Over the entire period 1988 to 2008, the nominal awards increased by 150% and by 30% in real terms. Wages share of the national economy fell significantly after 1988. The paper examines the implications of this for macroeconomic stabilization. The trade unions did engage in catch-up after 2000 but by then the factors underlying economic growth switched from exports to a credit fuelled bubble in building and construction and the demand for non-traded services. The explosion in pay awards, after 2000, was a destabilizing factor as they increased the vulnerability of the economy to an economic downturn and undermined the government’s response to the economic crisis in 2007. This paper suggests a framework that could be used as a basis for future “conversations” on how to conduct wage negotiations. The main proposal is to put inflation, productivity and “other factors” centre stage in new, transparent, negotiations. With regard inflation, the proposal is for the partners to agree real, not nominal, pay awards. This would entail ex post pay adjustments depending on the extent of the unanticipated inflation. The current situation is that there is no additional change to nominal earnings and the effect of unanticipated inflation falls entirely on the trade unions and their members. A compromise situation would be 50/50 split of the inflation burden being shared between the trade unions and the government. The downsize to this is that the government no longer has certainty with regard to public sector pay. The end-year payment to the unions is unknown and this could have serious implications in forming the annual fiscal budget. A positive side-effect is that the government would, most likely, adopt an inflation target to minimize the inflation-compensation payments. Currently, there are no specific anti-inflationary policy objectives in place. The paper, however, goes beyond the inflation issue and suggests that productivity and “other factors” become center stage in wage negotiations and are not an add-on as in the case of the nurses dispute in 2019. Overall, the paper concludes that there is much to be learned from the experience of pay awards between 1988 and 2008 and this should be used to design more effective pay award agreements in the future.
(read before the Society, 24 January 2019)
Keywords: national wage agreements; Central Statistics Office earnings data; nominal and real earnings; unanticipated inflation; public sector productivity; macroeconomic stabilization; 314.15